PUBLIC UNDERSTANDING OF HALAL INVESTMENT: QUALITATIVE STUDIES IN URBAN COMMUNITIES - Syamsiah, Syamsiah; Kara, Muslimin; Bakry, Muammar; Abdullah, Muhammad Wahyuddin (International Journal of Multidisciplinary Research and Literature, 2024)
This study investigates the conceptualization of halal investment among urban communities using a qualitative methodology. Even though most participants know that halal investments must adhere to syariah principles, the study discovered that they frequently rely solely on the syaria label without further investigating the structure and mechanisms of the investment product. Discovered through in-depth interviews, focus group discussions (FGDs), and observations. The primary challenges are insufficient education and a lack of more comprehensive and detailed information regarding halal investment products. Research participants indicated extensive training and seminars necessary to comprehend the selection of syaria-compliant investment products. Based on these findings, it is clear that syaria financial institutions are responsible for enhancing information transparency and strengthening education programs to assist the general public in making investment decisions that are truly by syaria principles